Merry go round or roller coaster? a demonstration of couples' psychotherapy - Nelson, Vivian; Roller, Bill, 1947-; Berkeley Group Education Foundation; Berkeley Group Therapy Education Foundation (Berkeley, Calif. : Berkeley Group Education Foundation, 2005)
A video training document intended to assist the practicing clinician.
A campion DVD "Prequel" to Merry go round or roller coaster? also issued.
DVD.
Keywords: Marriage counseling